Victim or Accomplice?: Crime, Medical Malpractice, and the Construction of the Aborting Woman in American Case Law, 1860s-1970 - Reagan, Leslie (Columbia Journal of Gender and Law, 2001)
The state legislators who, in the 1860s and 1870s, passed laws that for the first time criminalized abortion at all stages of pregnancy envisioned the aborting woman as an active agent, one who searched out abortion services in order to avoid the reproductive duties of marriage. “Fashionable” and “well-to-do” married women, mid-nineteenth-century anti-abortion commentators charged, filled the offices of abortionists. These “selfish” women had been known to declare “that they have neither the time nor the inclination to nurse babies.”‘ This image of the aborting woman, which provoked fears of feminism and fears that non-white and Catholic groups would soon outpopulate white Protestants, inspired lawmakers to criminalize abortion. Anyone who aided a woman’s efforts to end a pregnancy, whether by providing information, drugs and instruments, or inducing an abortion, and in some states the woman as well, could be prosecuted under the nation’s new criminal abortion laws. The woman who aborted was the villain in this mid-nineteenth- century anti-abortion story. Yet when the new criminal laws were put into practice, the representation of the aborting woman dramatically changed. Despite the consensus that produced the criminal abortion laws, the character of the aborting woman was a subject of legal debate throughout the century of illegal abortion. The judiciary was repeatedly asked whether the woman who had an abortion was an “accomplice” in the crime of illegal abortion or a “victim” of the criminal abortionist. The designation of the aborting woman as victim or accomplice in the courtroom could significantly affect trial outcomes. One definition cast the woman as passive object of violence, the other, as active agent in crime. The debate, carried out in courtrooms and recorded in appellate opinions, offers an opportunity to investigate judicial thinking not only about sexuality and gender, but also about the dual responsibility of the state to protect the health and safety of its citizens and to punish those who violated the law. Finally, analysis of jury actions affords a glimpse of the views of ordinary citizens regarding women, abortion, and the duties of physicians.